Estudio de factibilidad para la creación de un centro de desarrollo comunitario del sector ciudad del norte parroquia venus del río Quevedo cantón Quevedo, año 2015 - Bravo Zambrano, Diana Abigail (2016)
This research was conducted in the area of City North, pertaining to the canton Quevedo, to determine the feasibility of creating a Centro de Desarrollo Comunitario en el sector Ciudad del Norte parroquia Venus del Río Quevedo cantón Quevedo. The research is the pose in order to promote and create a source of work through training and considering that most of the population are street vendors and workers with minimum income that allows them to have better quality of life. The results were obtained through field research, and through a survey of the inhabitants of the northern sector of the city to get relevant answers on the need to carry out this project. The feasibility of the project for the implementation of community development center in Sector Ciudad del Norte, the interest shown by the public to have the opportunity to learn a short-term activity that will generate income for their welfare is determined the of his family. The total investment of the project is estimated at $ 11 852, $ 82, which will be financed by 80% with a bank credit and 20% are own contribution of the investor. The financial analysis leads to the conclusion that the project is feasible economically and financially viable, in addition to the acceptance of the community and establish the parameters required for project implementation.